Ambiente visual de conceptos asociados la lógica proposicional y predicados. (2017)
Implementation of a software that is intended to help students and professors with the learning of the propositional and predicate logic, which are the axis of the Information Technology & Computer Science Engineering. All the process of development of this software and its final result is described in these documents with a user guide.